Sumudu residual power series method to solve time-fractional Fisher’s equation - Rajendra Pant; Geeta Arora; Homan Emadifar; Ahmed A. Hamoud (Mathematics Open, 2025)
In this paper, the one-dimensional nonlinear temporal fractional-order Fisher’s equation is solved by using the Sumudu residual power series method (SRPSM), a powerful computing technique. This method combines the RPSM and Sumudu transform to provide approximations of solutions using the notion of limit, in contrast to the standard residual power series method, which necessitates computing fractional derivatives. With reference to the equation under consideration, this work compares and validates the solution obtained by using the considered method. The applicability, effectiveness, and dependability of the provided strategy were confirmed through the analysis of this equation and numerical simulations.